The Impact of Boss Phubbing on Teacher Self-Efficacy and Well-Being in Coastal Schools During the Digital Era - Oktarina Oktarina; M Iqbal Arrosyad; Widia Abela; Muhammad Eka M. Simbolon (Universitas Wahid Hasyim Semarang, 2025)
This study aims to analyze the impact of boss phubbing on teachers’ self-efficacy and teacher wellbeing in coastal-area schools within the context of digital-era educational management. Data were collected through a cross-sectional survey of teachers in coastal schools with a total sample of 206 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Jamovi 2.6.23 software. The findings indicate that boss phubbing does not directly affect teacher wellbeing but has a negative impact on teachers’ self-efficacy, which in turn plays a significant role in enhancing teacher wellbeing. These results highlight the importance of teachers’ self-efficacy as a mediator in reducing the negative effects of supervisors' digital behavior on teacher wellbeing in the digital era. Practical implications suggest that school management should pay attention to leaders’ digital behavior and foster teachers’ self-efficacy to improve work quality and teacher wellbeing. The limitations of this study include its cross-sectional design and the sample being limited to coastal-area schools; therefore, future research is recommended to employ longitudinal designs and consider additional moderating variables such as social support and organizational culture.